Potential of Viruses as Environmental Etiological Factors for Non-Syndromic Orofacial Clefts - Messias, Thiago S.; Silva, Kaique C. P.; Silva, Thiago C. [UNESP]; Soares, Simone (MDPI, 2024)
In this study, we analyzed the potential of viral infections in the species Homo sapiens as environmental causes of orofacial clefts (OFCs). A scoring system was adapted for qualitatively assessing the potential of viruses to cause cleft lip and/or palate (CL/P). This assessment considered factors such as information from the literature, nucleotide and amino acid similarities, and the presence of Endogenous Viral Elements (EVEs). The analysis involved various algorithm packages within Basic Local Alignment Search Tool 2.13.0 software and databases from the National Center for Biotechnology Information and the International Committee on Taxonomy of Viruses. Twenty significant viral species using different biosynthesis strategies were identified: Human coronavirus NL63, Rio Negro virus, Alphatorquevirus homin9, Brisavirus, Cosavirus B, Torque teno mini virus 4, Bocaparvovirus primate2, Human coronavirus HKU1, Monkeypox virus, Mammarenavirus machupoense, Volepox virus, Souris mammarenavirus, Gammapapillomavirus 7, Betainfluenzavirus influenzae, Lymphocytic choriomeningitis mammarenavirus, Ledantevirus kern, Gammainfluenzavirus influenzae, Betapolyomavirus hominis, Vesiculovirus perinet, and Cytomegalovirus humanbeta5. The evident viral etiological potential in relation to CL/P varies depending on the Baltimore class to which the viral species belongs. Given the multifactorial nature of CL/P, this relationship appears to be dynamic.
Keywords: cleft lip; cleft palate; etiology; mosquito-borne viruses; pathogenesis; viruses